Utilization of Smart APPS Creator (SAC) as Alternative Media for Application-Based Learning: Rubik (Rumah Bahasa Indonesia Kita) - Zahrani , Nadilah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
The purpose of this study was to determine the meaning of application-based learning media during the pandemic and to be able to provide new innovations to the community in creating the RUBIK application as a learning tool, especially Indonesian language subjects. The method in this study uses a quantitative method in the form of a questionnaire conducted by researchers in order to know the respondents' assessment of the RUBIK application in learning. The results of this study indicate that the RUBIK application has meaning in learning and this application is considered by the respondents to be quite attractive, efficient and effective when applied in the learning process. The only drawback in this research is that the learning is one-way. In addition, this application also has obstacles such as the type of smartphone that does not support installing the RUBIK application. And the full memory on the respondent's cellphone hinders the learning process using this RUBIK application.